ChemInform Abstract: High‐Voltage Cathode Materials for Lithium‐Ion Batteries: Freeze‐Dried LiMn0.8Fe0.1M0.1PO4/C (M: Fe, Co, Ni, Cu) Nanocomposites. Issue 22 (15th May 2015) - Iturrondobeitia, Amaia; Goni, Aintzane; Gil de Muro, Izaskun; Lezama, Luis; Kim, Chunjoong; Doeff, Marca; Cabana, Jordi; Rojo, Teofilo
Abstract: LiMn0.8 Fe0.1 M0.1 PO4 /C (M: Fe, Co, Ni, Cu) nanocomposite cathode materials are prepared by freeze‐drying of aqueous solutions of citric acid, Mn(OAc)3, LiOH, NH4 H2 PO4, and M(OAc)2 in stoichiometric quantities (‐80 °C, 48 h, 3 x 10 ‐1 mbar).